1999
DOI: 10.1002/(sici)1521-4141(199908)29:08<2420::aid-immu2420>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally long CDR3H region with multiple cysteine residues in functional bovine IgM antibodies

Abstract: We analyzed VDJ and VJ rearrangements in IgM‐secreting B lymphocytes from a cow infected with bovine leukemia virus (BLV). BLV causes expansion of CD5+ and IgM+ B lymphocytes regardless of antigen specificity. The data showed that single point mutations contribute to the diversification of IgM antibodies. The most striking observation, however, is that approximately 9 % of theVDJ rearrangement in IgM‐secreting B cells encode an exceptionally long third complementarity‐determining region of the heavy chain (CDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 18 publications
7
103
0
3
Order By: Relevance
“…The presence of additional cysteine residues has also been observed in cow (16), shark (43), and members of Camelidae (44 -46). V H sequences in cow sometimes have exceptionally long CDR3, with reports of sequences of up to 61 amino acid residues (16). These long CDR3 may contain six or eight cysteine residues, indicating the presence of three or four cysteine bridges.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of additional cysteine residues has also been observed in cow (16), shark (43), and members of Camelidae (44 -46). V H sequences in cow sometimes have exceptionally long CDR3, with reports of sequences of up to 61 amino acid residues (16). These long CDR3 may contain six or eight cysteine residues, indicating the presence of three or four cysteine bridges.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs. Cows, however, produce antibodies with HCDR3s that average ~26 amino acids in length with an ultralong subset (10–15% of the repertoire) that can be over 70 amino acids in length 46,8,9,16 . Previous work has shown that repeated immunization over multiple years with a non-well-ordered Env trimer in cows can lead to some neutralization breadth in the immunoglobulin-rich colostrum 1719 , although with relatively low potency.…”
Section: Main Textmentioning
confidence: 99%
“…In some areas, the approximate infection rate in adult cows can reach 30 -40%, as assessed by the presence of serum Abs. Approximately 30% of BLV-infected cattle develop a benign persistent lymphocytosis following infection, characterized by a polyclonal expansion of B cells generally expressing IgM and CD5 molecules at the cell surface (1)(2)(3)(4). Under these conditions, the level of lymphocytosis is generally in the range of 20,000 -80,000 lymphocytes/ l. After a prolonged incubation period, ϳ1-5% of infected cows will develop lymph node (LN) tumors.…”
mentioning
confidence: 99%